Penyuluhan Kesehatan Dampak Rokok Bagi Kesehatan Siswa Siswi SD Negeri 8 Benteng - Ula, Zumrotul; Ramli, Rachmad; Nurhaedah, Nurhaedah; Idris, Idris; Arda, Darmi; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Smoking behavior is a public health problem because it can cause various diseases and even death. Smokers have a 2-4 times greater risk of developing coronary heart disease and a higher risk of sudden death. Smoking also has a negative impact on passive smokers, passive smokers inhale more substances contained in cigarette smoke than active smokers, passive smokers inhale 2 times more nicotine, 5 times more carbon monoxide, 3 times more tar, and 50 times more more chemicals that are harmful to health. From this education, knowledge is also provided on how to prevent smoking. With health education provided to teenagers, teenagers will increase their knowledge about the dangers of smoking.